2019
DOI: 10.1177/1535370219831225
|View full text |Cite
|
Sign up to set email alerts
|

The effects of N-acetylcysteine on radiotherapy-induced small intestinal damage in rats

Abstract: Six million cancer patients worldwide receive radiotherapy, either alone or in combination with other cancer treatments annually. The purpose of this study was to investigate, at the structural and molecular levels, the protective effect of N-acetylcysteine (NAC), a powerful antioxidant, against radiotherapy-induced damage on the intestinal system. Three study groups were constituted: control (group 1: no radiotherapy), radiotherapy (RT; group 2), and RT + NAC (group 3). The NAC group received 300 mg/kg NAC or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…The histopathological examination of liver tissue supported the biochemical results and confirmed the ameliorative effect NAC and Se against ionizing radiation and / or CCl 4 . These results are in agreement with the findings of Mercantepe et al (2019) who observed that NAC manifested protective effect at the structural and molecular levels against gastrointestinal syndrome resulting from radiotherapy. Additionally, Se supplementation improved liver histopathological criteria against bisphenol Ainduced hepatotocixity in rats (Abdel Samie et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The histopathological examination of liver tissue supported the biochemical results and confirmed the ameliorative effect NAC and Se against ionizing radiation and / or CCl 4 . These results are in agreement with the findings of Mercantepe et al (2019) who observed that NAC manifested protective effect at the structural and molecular levels against gastrointestinal syndrome resulting from radiotherapy. Additionally, Se supplementation improved liver histopathological criteria against bisphenol Ainduced hepatotocixity in rats (Abdel Samie et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The results suggest that NAC and sodium selenite have the ability to increase the antioxidant capacity, quench free radicals and prevent cellular membranes from being damaged by free radicals. These results come in accordance with those of Mercantepe et al (2019) who reported that NAC exhibited protective effects in rats against radiation-induced intestinal damage. Pei et al (2018) demonstrated that NAC directly interacts with the free radicals via its thiol side -chain.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, an increased caspase-3 activation signal, suggesting apoptosis stimulation in intestinal crypts, is also involved in GIARS pathology [ 9 ]. The manifestation of GIARS in mammals is associated with weight loss, decreased nutrient absorption, profuse diarrhea and progressive dehydration, as well as bacterial translocation into the bloodstream [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%